2021
DOI: 10.1007/s10665-021-10137-z
|View full text |Cite
|
Sign up to set email alerts
|

Introducing pre-impact air-cushioning effects into the Wagner model of impact theory

Abstract: In this analysis, we consider the effects of non-quiescent initial conditions driven by pre-impact air–water interactions on the classical Wagner model of impact theory. We consider the problem of a rigid, solid impactor moving vertically towards a liquid pool. Prior to impact, viscous forces in the air act to deform the liquid free surface, inducing a flow in the pool. These interactions are then incorporated as initial conditions in the post-impact analysis. We derive expressions for the size of the effectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This cushioning effect can soften the impact so much that the schlieren imaging cannot detect the pressure waves for some impacts (see, for example, Supplemental Movie 4 ). Previous studies do not agree on the magnitude of the pressure on the impacting surface when air cushioning is significant 29 31 , but we would expect the pressure to scale with 30 , which upon reflection off the free surface results in Daou et al 20 experimentally showed that even in the presence of an air layer, the pressure in the near field continues to scale with the water hammer pressure (i.e., ( 2 ) still applies). Hence, combining ( 1 ), ( 2 ) and ( 6 ) and simplifying shows that even at the lowest α the impact must exceed a critical velocity for cavitation to occur; As the ambient gas pressure, P a m b , affects the amount of trapped air, and the cushioning effect, the value of k 2 should change with gas properties, decreasing with lower P a m b .…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This cushioning effect can soften the impact so much that the schlieren imaging cannot detect the pressure waves for some impacts (see, for example, Supplemental Movie 4 ). Previous studies do not agree on the magnitude of the pressure on the impacting surface when air cushioning is significant 29 31 , but we would expect the pressure to scale with 30 , which upon reflection off the free surface results in Daou et al 20 experimentally showed that even in the presence of an air layer, the pressure in the near field continues to scale with the water hammer pressure (i.e., ( 2 ) still applies). Hence, combining ( 1 ), ( 2 ) and ( 6 ) and simplifying shows that even at the lowest α the impact must exceed a critical velocity for cavitation to occur; As the ambient gas pressure, P a m b , affects the amount of trapped air, and the cushioning effect, the value of k 2 should change with gas properties, decreasing with lower P a m b .…”
Section: Resultsmentioning
confidence: 83%
“…This allows cavitation to occur at lower impact velocities and k 2 decreases to k 2 ≈ 0.0022 for P a m b ≤ 1/2 atm, corresponding to U o ≃ 3.3 m/s in water. Other studies have shown that the thinness of the air film and the rapid contact line motion cause the gas viscosity 31 , 32 , gas density 32 , rarefied gas effects 33 , and gas speed of sound 29 to affect the air cushioning. Hence, we expect that the minimum velocity for cavitation and k 2 likely depend on each of these parameters as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of droplet post-impact theory onto deformable surfaces has been tackled previously 13,15 by ignoring the air cushioning phase and the entrapped air. However, these features do influence the post-impact dynamics, 26,70 and so questions remain on how this occurs in impact on deformable surfaces. One possible alternative to the air cushioning model presented here and the classic Wagner model of impact theory would be to use direct numerical simulation to analyze how air cushioning effects influence post-impact dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the air cushion is especially important for phenomena at the very initial stage, when the instantaneous Froude number is tremendously large. The detailed behaviour of the air cushion and its effect on various aspects of the impact, such as splash, pressure and force, are studied in, for example, Bouwhuis et al (2015), Jain et al (2021), Moore (2021), Hicks et al (2012).…”
Section: Introductionmentioning
confidence: 99%